Adenocarcinoma and neuroendocrine tumor arising within presacral teratoma associated with Currarino syndrome: A case report - Chatani, Shohei; Onaya, Hiroaki; Kato, Seiichi; Inaba, Yoshitaka (Indian Journal of Radiology and Imaging, 2019)
We present a case of a 59-year-old woman with a malignant tumor arising within presacral teratoma associated with Currarino syndrome (CS). A characteristic crescent-shaped sacrum was detected on preoperative image examination and the presacral mass was pathologically diagnosed as a malignant tumor associated with CS. To our knowledge, this is the first case report of presacral teratoma associated with CS coexisting with both adenocarcinoma and a neuroendocrine tumor.
Keywords: Adenocarcinoma; Currarino syndrome; neuroendocrine tumor; teratoma